Computational analysis of wind interactions for comparing different buildings sites in terms of natural ventilation. (October 2015) - Mora-Pérez, Miguel; Guillén-Guillamón, Ignacio; López-Jiménez, P. Amparo
Highlights: A particular building location can be selected attending to natural ventilation. A methodology is proposed to optimize sites considering buildings natural ventilation. A validated CFD model is used to represent outdoor and indoor spaces. In this case, the best location, from two real possible solutions, is evaluated. Abstract: Nowadays building designers have to face up to new strategies to achieve the best sustainable building designs. Well planned natural ventilation strategies in building design may contribute to a significant reduction on building's energy consumption. Natural ventilation strategies are conditioned to the particular location of each building. To improve natural ventilation performance of a building, the analysis of the influence of the location and the surrounding buildings on wind flow paths around the design building is a must. New computational tools such as Computational Fluid Dynamics (CFD) are particularly suited for modelling outdoor wind conditions and the influence on indoor air conditions prior to building construction. Hence, reliable methodologies are necessary to support building design decisions related to naturally ventilated buildings prior to construction. This paper presents a case study for the selection of the best future building location attending to natural ventilation behaviour inside the building, conditioned by different evolving environment. A validated CFD model is used to represent outdoor and indoor spaces. The methodology explains how to qualitatively and quantitatively analyze wind paths around and through a building to quantify the natural ventilation performance. The best location, from two real possible solutions, is then selected.